An exploratory study on functional connectivity after mild traumatic brain injury: Preserved global but altered local organization. Issue 9 (22nd August 2022) - Kim, Eunkyung; Seo, Han Gil; Seong, Min Yong; Kang, Min‐Gu; Kim, Heejae; Lee, Min Yong; Yoo, Roh‐Eul; Hwang, Inpyeong; Choi, Seung Hong; Oh, Byung‐Mo
Abstract: Introduction: This study aimed to investigate alterations in whole‐brain functional connectivity after a concussion using graph‐theory analysis from global and local perspectives and explore the association between changes in the functional network properties and cognitive performance. Methods: Individuals with mild traumatic brain injury (mTBI, n = 29) within a month after injury, and age‐ and sex‐matched healthy controls ( n = 29) were included. Graph‐theory measures on functional connectivity assessed using resting state functional magnetic resonance imaging data were acquired from each participant. These included betweenness centrality, strength, clustering coefficient, local efficiency, and global efficiency. Multi‐domain cognitive functions were correlated with the graph‐theory measures. Results: In comparison to the controls, the mTBI group showed preserved network characteristics at a global level. However, in the local network, we observed decreased betweenness centrality, clustering coefficient, and local efficiency in several brain areas, including the fronto‐parietal attention network. Network strength at the local level showed mixed‐results in different areas. The betweenness centrality of the right parahippocampus showed a significant positive correlation with the cognitive scores of the verbal learning test only in the mTBI group. Conclusion: The intrinsic functional connectivity after mTBI is preserved globally, but is suboptimally organized locally in several areas. This possibly reflects the neurophysiological sequelae of a concussion. The present results may imply that the network property could be used as a potential indicator for clinical outcomes after mTBI.